Cybersecurity Vulnerabilities at the Indonesia–Papua New Guinea Border: Securitization Asymmetry, Institutional Gaps, and Diplomatic Escalation - Putri, Dewi Anjani Kartika; Maksum, Ali (Universitas Cenderawasih, 2026)
This study aims to examine how cybersecurity vulnerabilities at the bilateral border between Indonesia and Papua New Guinea (PNG) create risks of diplomatic crises through institutional gaps and asymmetric threat perceptions. By adopting a qualitative research approach, and drawing on securitization theory and constructivism in IR, this article reveals four key findings. First, Indonesia and PNG lack formal bilateral agreements on cyber incident response and attribution procedures. Second, asymmetric securitization exists whereby Indonesia over-securitizes cyber threats while PNG under-securitizes them, creating misaligned threat perceptions. Third, the absence of shared norms prevents a coordinated bilateral response. Fourth, historical trust deficits facilitate rapid escalation from technical incidents to diplomatic crises. Theoretically, these findings demonstrate how securitization asymmetry operates at the bilateral level, and practically, they identify mechanisms for preventing cyber incidents from disrupting diplomatic stability in the Indo-Pacific. KEYWORDS Border; Cybersecurity Vulnerabilities; Indonesia; Papua New Guinea; Securitization Asymmetry